Why Infusion of Virtue Matters? A Study on Thomas Aquinas’s Virtues in a Person’s Ethical Decision - Ludji, Irene (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
In this article, I discuss the importance of St. Thomas Aquinas’s infused virtue in living an ethical Christian life, a critical element of church formation. The research question in this article answered the importance of infused virtue in understanding the goodness of a person's moral life as a church member. The method used in this article is a literature study that focuses on the work of Thomas on acquired and infused virtue ethics. Thomas’s virtue ethics is demonstrated to be a complete set of ethics, that does not only focus on acquired ethics. Moral and intellectual virtues are not enough for human beings to achieve the proper purpose of their life by themselves. Therefore, human beings need the infusion of virtues as a part of God’s grace that will elevate their understanding of God’s universal moral order. There are three parts to this article, in the first part of the article, I present a critique of the belief that Christian ethics should rely only on habit as something that can be acquired through practice. In the second part of the article, I discuss Thomas’s virtue ethics by briefly introducing his concept of natural law and its relation to virtue. In the last part of this article, I provide a conclusion on why I think infused virtue matters.